Bridging the Gap between Advantaged and Disadvantaged Children: - Caroline Fitzpatrick (South African Journal of Childhood Education, 2014)
Reducing the economic and social burden associated with poor academic achievement represents an urgent social concern. Increasingly research suggests that child characteristics in kindergarten play an important role in charting courses towards academic success. Although math and reading skill are important predictors of later achievement, executive function skills which underlie children’s ability to focus attention and become autonomous, self-directed learners are also likely to play a key role in later adjustment to school. Disadvantaged children perform more poorly on tests of achievement and executive functions.  Furthermore, executive functions have been found to partially account for the relationship between socioeconomic status and later achievement. It is possible to target executive functions in at-risk children using specific interventions. Not only are these interventions effective, they are also cost effective. It is proposed that increasing efforts towards promoting executive functions in preschool-aged children represents a promising strategy for reducing economically-based disparities in the education and eventual life chances of individuals.